Ambulation during Neuraxial Analgesia in Obese Patients: A Pilot Study - Suresh, Sunitha; Seiler, F. Arran; Arnolds, David; Gonzalez, Maritza; Cole, Naida; Silver, Richard; Scavone, Barbara; Dude, Annie (American Journal of Perinatology, 2025)
Objective Prior studies have yielded mixed results regarding ambulation with neuraxial analgesia and labor outcomes, and studies did not include a significant obese population. We sought to evaluate the feasibility of ambulation with optimized neuraxial analgesia in laboring nulliparous obese patients.Study Design This was a pilot study at the University of Chicago (approval no.: IRB 19-1600, CT NCT04504682). Inclusion criteria were delivery BMI of ≥35 kg/m2, nulliparity, and term gestation. Contraindications to ambulation or vaginal delivery conferred ineligibility. Combined spinal-epidural analgesia was initiated per our institution's policy. Following epidural catheter placement, serial blood pressure measurements and motor assessments including a straight leg test and a step stool test were completed per safety protocol. Patients who passed these assessments were enrolled. Patients were encouraged to ambulate for 20 minutes every hour while on fetal and uterine telemetry. Ambulation was discouraged after complete dilation. Demographics and delivery outcomes were collected. Our primary objective was to evaluate feasibility through acceptability, and safety via the number of falls, and percentage of patients with any ambulation. The study was closed early due to enrollment difficulties and in the setting of the COVID-19 pandemic.Results A total of 105 patients were identified for the trial: 20 were ineligible for the study, 20 could not be approached, and 40 declined study participation, leaving 25 patients who consented. Of those 25, 14 completed the study. Out of 14 participants, 11 were ambulated. The average BMI of these participants was 43 kg/m2. No patients fell during the trial.Conclusion A pilot trial of ambulation during neuraxial analgesia among an obese nulliparous population demonstrated no safety concerns, but with concern regarding feasibility as there was low acceptance.Key Points
Keywords: obesity; labor; anesthesia